Evaluasi Efektivitas Pidana Mati Bersyarat Terhadap Tindak Pidana Narkotika di Indonesia - Zahra Aura Diba; Ifahda Pratama Hapsari (Universitas Semarang, 2025)
This study evaluates the effectiveness of the conditional death penalty as regulated under Articles 100–101 of Law Number 1 of 2023 on the Indonesian Criminal Code in addressing narcotics crimes, considering that approximately 93% of death row inmates are convicted of narcotics-related offenses. The ten-year probation period raises legal concerns due to the absence of objective criteria for assessing prisoners’ behavioral changes, thereby affecting legal certainty and substantive justice. This research employs a normative juridical method using statutory, conceptual, and analytical approaches through grammatical, systematic, historical, and teleological interpretation of the 2023 Criminal Code, the Narcotics Law, and human rights instruments. The findings indicate that the conditional death penalty constitutes a significant penal innovation with the potential to balance public protection against narcotics threats and respect for the right to life and restorative justice principles; however, its effectiveness is constrained by the lack of implementing regulations, the absence of multidisciplinary evaluation standards, and limited correctional institutional capacity. The novelty of this study lies in integrating punishment effectiveness, human rights, and restorative justice perspectives while formulating the need for objective evaluation parameters during the probation period. This study recommends the enactment of implementing regulations, the establishment of independent assessment teams, and the strengthening of correctional resources to ensure a fair, accountable, and human-oriented narcotics sentencing system. Penelitian ini mengevaluasi efektivitas pidana mati bersyarat sebagaimana diatur dalam Pasal 100–101 Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana dalam penanggulangan tindak pidana narkotika di Indonesia, mengingat sekitar 93% terpidana mati berasal dari perkara narkotika. Pengaturan masa percobaan selama sepuluh tahun menimbulkan persoalan yuridis akibat ketiadaan kriteria objektif untuk menilai perubahan perilaku terpidana, sehingga berimplikasi pada kepastian hukum dan keadilan substantif. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan analitis melalui penafsiran gramatikal, sistematis, historis, dan teleologis terhadap KUHP 2023, Undang-Undang Narkotika, serta instrumen hak asasi manusia. Hasil penelitian menunjukkan bahwa pidana mati bersyarat merupakan inovasi pemidanaan yang berpotensi menyeimbangkan perlindungan masyarakat dari bahaya narkotika dengan penghormatan terhadap hak hidup dan prinsip keadilan restoratif, namun efektivitasnya masih terhambat oleh ketiadaan aturan pelaksana, belum adanya standar evaluasi berbasis ilmu multidisipliner, serta keterbatasan kapasitas lembaga pemasyarakatan. Kebaruan penelitian ini terletak pada integrasi perspektif efektivitas pemidanaan, hak asasi manusia, dan keadilan restoratif sekaligus perumusan kebutuhan parameter evaluasi objektif selama masa percobaan. Penelitian ini merekomendasikan pembentukan regulasi pelaksana, tim evaluasi independen, dan penguatan sumber daya pemasyarakatan guna mewujudkan sistem pemidanaan narkotika yang adil, akuntabel, dan berorientasi kemanusiaan.